SPATIAL MODELING FOR DETERMINING THE SEATING OF MALEO BIRDS IN THE HUNGAYONO CONSERVATION AREA, EAST SUWAWA DISTRICT - Irma Zein Moghuri; Sunarty S Eraku; Daud Yusuf (Geographica: Science and Education Journal, 2021)
This research is a research conducted in the Hungayono Conservation Area, East Suwawa District. The purpose of this study was to determine the distribution of Maleo bird eggs. The methods used in this research are the model builder, Land Surface Temperature (LST), and Normalized Difference Vegetation Index (NDVI). Data collection techniques through observation and documentation. The results of the research that have been conducted show that the distribution of Maleo Bird eggs in the Hungayono Conservation Area is divided into three criteria, namely, potential one has a land area of 549.947 ha, potential two with an area of 19774.3 ha, and potential three has a land area of 6220.51. ha, so that there are differences in the potential land area of Maleo birds which are categorized based on predetermined criteria. Referring to this fact, the part of the area which is the habitat for the Maleo Bird's nesting ground should always be preserved to protect the Maleo Bird from the threat of extinction.